Characteristics of chronic obstructive pulmonary disease patients with depressive disorder - Čekerevac Ivan; Lazić Zorica; Novković Ljiljana; Petrović Marina; Ćupurdija Vojislav; Željko Todorović; Đurđević Predrag; Ilić-Dudvarski Aleksandra; Suša Romana (Srpski Arhiv za Celokupno Lekarstvo, 2017)
Introduction/Objective. The origin of depressive disorder in chronic obstructive pulmonary disease (COPD) patients is still not completely known and probably is caused by various factors. The aim of this study is to establish the most important characteristics of COPD patients who have depressive disorder. Methods. Eighty-nine COPD patients and 65 demographically-matched referents without COPD were included. All the patients underwent lung function examination, and gas exchange, nutritional status, dyspnoea level by the modified Medical Research Council (mMRC) scale and exercise tolerance were also assessed, as well as depressive disorder by Hospital Anxiety and Depression Scale (HADS) and Geriatrics Depression Scale (GDS) and quality of life by St. George’s Respiratory Questionnaire (SGRQ). Results. Depressive disorder has been found in 30.3% of COPD patients evaluated by HADS and 25.3% of COPD patients evaluated by GDS. When COPD subjects were stratified by forced expiratory volume in 1 second (FEV1) categorization, all subgroups were more likely to have depressive disorder, according to HADS and GDS, relative to referents with the odds ratio highest (3: 95% confidence interval 1.6–4.9) among those with the FEV1 < 30%. COPD patients with depressive disorder (HADS) compared to non-depressed patients had (differences in mean values) higher intensity of smoking [6.9 (0.5–10.1)], lower body mass index [-4.9 (-7.2–5.4)], lower value of FEV1% [-8.3 (-16.3–1.2)] , higher value of total lung capacity (%) [17.8 (2.3–28.4)], higher mMRC score (1.07 (-1–3.0), and higher SGRQ – giving a total score of 32.9 (24.1–40.3). Conclusion. Evaluation of depressive disorder should be considered in every patient with COPD, especially in patients with greater degree of airflow limitation and lung hyperinflation, dyspnoea level and malnourished.